Silicon Mitigates the Effects of Nitrogen Deficiency in Plants - Silva Campos, Cid Naudi; da Silva, Bianca Cavalcante [UNESP] (Springer Nature, 2023)
Silicon (Si) application attenuates plant stress under nutritional disorder conditions, such as nitrogen (N) deficiency, which directly reflects on the crop yields. The action mechanisms of Si in the mitigation of the damaging effects caused by N deficiency are: increased cell wall stiffness and lignin production, improved leaf architecture, increased water-use efficiency, greater integrity of cell membranes, increased chlorophyll and carotenoid contents, increased quantum efficiency of photosystem II, increased photosynthesis, increased proline and glycine-betaine production, increased phenolic and antioxidant compounds, and decreased production of H2O2 and malondialdehyde. This chapter aims to highlight the effects of Si in mitigating the biochemical and physiological damage caused by N deficiency. Applying Si is a helpful strategy for crop management aiming to reduce losses caused by abiotic stress conditions, especially by N deficiency. It is important to highlight the need for further investigations to better understand the nutritional, biochemical, and physiological effects of Si on N-deficient plants.
Keywords: Abiotic stress; Beneficial element; Macronutrient; Nutritional disorder; Plant nutrition